Views of the University Students Towards Implementation of Learning Management System to Enhance Blended Teaching and Learning: Experiences from UDOM e-Classroom - Paul Loisulie (Indonesian Educational Research Journal, 2024)
This study explored the views of students towards adoption of the Learning Management System in enhancing teaching and learning processes. It used the UTAUT lenses to organize the views of students about eclassroom. The study focused on the experiences of UDOM students who have the experience of using the eclassroom system as the LMS. It was the qualitative study which used an online qualitative survey to collect data from the participants from students in two consecutive years. About 315 participants were able to fill the online questionnaire. The conceptual content analysis technique was used for data analysis basing on the four constructs of the UTAUT as the predetermined themes. The findings show that students view use of LMS positively due to learning opportunities introduced, effectiveness, saving cost as well as saving time achieved during the interaction with the system. However, facilitating conditions are to be improved to remove barriers like poor network and security issues for smooth adoption of LMS by others. The study concludes that, adoption of LMS in universities is the right path to embrace since it is consistently proven by optimistic views of students that the system is more useful in terms of the four constructs of the UTAUT model. Key recommendation is that the institutions should be active enough to create a conducive environment as per the Tanzania Commission for Universities 2022 guidelines on online courses delivery and management.